Promosi Kesehatan Media Poster Membuang Sampah yang Baik dan Benar untuk Mengendalikan Penyakit Berbasis Lingkungan Jakarta Utara Tahun 2022 - Mayumi Nitami; Decy Situngkir; Mugi Wahidin (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2023)
The density of charters and the large number of people living around the banks of the Teluk Angke area in RT Teluk Gong. 05/08 Kelurahan Pejagalan resulted in an increase in the amount of waste of various types, ranging from food waste, plastic waste, fruit peel waste, used cans, etc. The purpose of this community service activity is to help the community in dealing with environmental-based diseases. The socialization method was carried out on health promotion in the abdimas scientific forum activities with the theme "Media Posters for Health Promotion Disposing of Good and Correct Garbage for Environment-Based Disease Control" using poster media for ± 15 minutes followed by questions and answers, posting posters in each resident's trash can, monitoring and evaluation. The results obtained from this study were changes in the behavior of participants about how to dispose of waste properly and correctly, thus increasing public awareness of how important it is if we dispose of waste properly and correctly so that we can control environmental-based diseases.